(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2023)
Purpose: In this study, the aim is to determine whether labour market institutions (LMI) variables impacted the unemployment rate in the Central and Eastern Europe (CEE) countries between 2000 and 2017. Methodology: Panel data methods that take cross-sectional dependence into account are used for the analysis. Results: Empirical findings show that real minimum wages, tax wedge, and union density do not impact the unemployment rate in Poland, Latvia, and Estonia, while these variables impact the unemployment rate in Slovakia, the Czech Republic, Slovenia, and Hungary. Conclusion: As a result of the research, it is concluded that the LMI variables do not have a substantial effect on the unemployment rate in Poland, Latvia, and Estonia. On the other hand, the LMI variables have a substantial impact on the unemployment rate in Slovakia, the Czech Republic, Slovenia, and Hungary. Therefore, it is understood that the LMI variables have an influence on the unemployment in only four out of seven CEE countries.